EVALUATION OF THE IMPLEMENTATION OF THE SCHOOL LITERACY MOVEMENT (GLS) PROGRAM IN BANTUL REGENCY - Andreanus Pattikawa Lbn Toruan; Nur Hidayanto Pancoro Setyo Putro; Sudiyatno Sudiyatno; Widowati Pusporini; Jeffri Dian Andika (Lembaga Penelitian Mahasiswa Penalaran UNM, 2025)
This study aims to evaluate the achievement and differences in the implementation of the School Literacy Movement (GLS) program in elementary schools in Bantul Regency. This evaluative research employed a mixed-methods approach, utilizing the CIPP evaluation model with a quantitative descriptive orientation. Data were collected through questionnaires and interviews, involving respondents consisting of teachers and elementary students from one public and one private elementary school, namely SD Muhammadiyah Bendo and SD Negeri Sutran. The results at SD Muhammadiyah Bendo indicate that 28.13% fall into the